Synergistic Effects of Organic and Potassium Fertilization on Soil Properties and Pinto Bean Performance - Seyedeh Sara Sohrabi Sedeh (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2026)
Low organic matter in many Iranian soils leads to soil structural degradation and reduced crop productivity. Applying chicken manure offers a cost-effective organic amendment that improves soil quality by supplying organic matter and nutrients through gradual release. This study aimed to evaluate the effects of chicken manure and potassium fertilizer on pinto bean yield and determine soil physical and chemical properties under field conditions. The experiment was arranged in a split-plot design within a randomized complete block design with three replications. Chicken manure was applied to main plots at four rates (0, 5, 10, and 15 t ha⁻¹), while potassium fertilizer, supplied as potassium sulfate (K₂O), was applied to sub-plots at four levels (0, 100, 175, and 250 kg ha⁻¹). Yield components of pinto bean and soil physical and chemical properties were measured. The results indicated that both chicken manure and potassium fertilizer significantly increased pinto bean seed yield, with the highest yield obtained at 15 t ha⁻¹ of chicken manure combined with 250 kg ha⁻¹ of potassium fertilizer. The application of both inputs also enhanced yield components, including number of pods per plant, harvest index, and seed protein content. Chicken manure significantly improved soil physical properties by increasing water infiltration rate, saturated moisture, and total porosity, while reducing bulk density. It also enhanced soil chemical properties by increasing electrical conductivity, soil organic carbon, and available phosphorus, as well as lowering soil pH. In contrast, potassium fertilizer primarily increased soil electrical conductivity and reduced the final infiltration rate. The results demonstrate that chicken manure substantially improves soil quality and pinto bean productivity. The integration of organic and chemical fertilizers can be considered an effective and sustainable nutrient management strategy for improving soil fertility in low-organic-matter soils.